TcSR62, an RNA-binding protein, as a new potential target for anti-trypanocidal agents - Níttolo, Analía G.; Chidichimo, Agustina M.; Benacerraf, Ana L.; Cardozo, Timothy; Corso, M. Clara; Tekiel, Valeria; De Gaudenzi, Javier G.; Levy, Gabriela Vanesa (Frontiers in Microbiology, 2025)
Trypanosomatids are parasites of health importance that cause neglected diseases in humans and animals. Chagas’ disease, caused by Trypanosoma cruzi, affects 6–7 millions of people worldwide, mostly in Latin America, most of whom do not have access to diagnosis or treatment. Currently, there are no available vaccines, and the antiparasitic drugs used for treatment are often toxic and ineffective for the chronic stage of infection. Therefore, exploration of new therapeutic targets is necessary and highlights the importance of identifying new therapeutic options for the treatment of this disease. Trypanosomatid genes are organized and expressed in a species-specific fashion and many of their regulatory factors remain to be explored, so proteins involved in the regulation of gene expression are interesting candidates as drug targets. Previously, we demonstrated that the TbRRM1 protein from T. brucei is an essential nuclear factor involved in Pol-II transcriptional regulation. TcSR62 is a TbRRM1 orthologous protein in T. cruzi, but little is known about its function. In this study, we used molecular modeling of the RNA-binding domains of the TcSR62 protein and computational molecular docking to identify TcSR62-specific drug candidates. We identified sorafenib tosylate (ST) as a compound with trypanocidal activity. Sorafenib tosylate showed promising half-maximal inhibitory concentration (IC50) for all parasite stages in vitro. Furthermore, overexpression of TcSR62 protein led to ST-resistant parasites, suggesting that the trypanocidal effect might be due to the inhibition of TcSR62 function. These results demonstrate that ST could be repurposed as a novel drug to treat Chagas’ disease.